The Efficacy of Genistein-Rich Edamame as a Prevention of Atherosclerotic Lesion in Abdominal Aorta: Study in Rats Model of Atherosclerosis - Rizky Aditya Fardhani; Reza Dian Pratama; Nani Maharani; Bahrudin; Yuriz Bakhtiar; M Ali Sobirin; Farmaditya EP Mundhofir (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Atherosclerosis is the main cause of ischemic heart disease which leads to death for people aged more than 40 years old. Genistein is an important isoflavone compound which may protect the blood vessels from endothelial injury. This research is to observe the efficacy of genistein rich edamame as a prevention for atherosclerotic abdominal aortic lesions that seen from abdominal aortic thickness and foam cells count. Method: Thirty rats were divided randomly into five groups and treated for 28 days. The negative control group was given food and drink ad libitum. The positive control group was induced for atherosclerosis using adrenaline 0.006 mg / 200 gr BW injected on the first day and then the next day was given egg yolk 5 gr / 200 gr BW on next day for 28 days. All of the treatment groups were induced for atherosclerosis and treated with genistein-rich edamame extract 5 mg / 200 gr BW, edamame extract 38 mg / 200 gr BW and atorvastatin 1.5 mg / 200 grBW. Data were analyzed using One Way ANOVA - post hoc Bonferroni test, Kruskal Wallis - Mann Whitney test, and Pearson correlation test. Results: There were significant differences (p<0,001) in abdominal aortic thickness and foam cells count between positive control group and treatment genistein-rich edamame extract, edamame extract and atorvastatin. There was a significant correlation between the abdominal aortic wall thickness and foam cells count (correlation coefficient value 0,753; p<0,001). Conclusion: The administration of genistein-rich edamame extract can prevent the thickening of abdominal aorta and foam cell formation. Genistein-rich edamame can prevent foam cells formation better than atorvastatin.